A tale of parallel integration processes: a gravity analysis of EU trade with Mediterranean and Central and Eastern European countries - Anna Ferragina; Giorgia Giovannetti; Francesco Pastore (Institute for the Study of Labor (IZA), 2005)
Despite the EU emphasis on the 1995 Barcelona process, trade integration with the Mediterranean (MED) countries is still underdeveloped. To contrast the success of EU integration with MED countries and that with the new EU members, we compute the trade potential of these EU partners from 1995 to 2002 using an out-of-sample methodology. The coefficients are taken from different panel estimators of the gravity equation relative to intra-EU trade. Our analysis suggests the existence of sizeable, unexploited trade potential with both groups of partners, although the ratio of potential to actual trade with the MED countries is much larger (from 1.7 to 2.5 times), more dispersed and stable compared to that with the CEECs. Moreover, the potential tends to converge to actual trade in a much longer time in the case of MED countries.
Keywords: C23; F15; F17; P45; P52; 330; MED agreemeents; EU eastward enlargement; gravity equation; trade potential